Salinity induces discontinuous protoxylem via a DELLA‐dependent mechanism promoting salt tolerance in Arabidopsis seedlings. Issue 1 (12th July 2022) - Augstein, Frauke; Carlsbecker, Annelie
Summary: Salinity is detrimental to plants and developmental adjustments limiting salt uptake and transport is therefore important for acclimation to high salt. These parameters may be influenced by xylem morphology, however how plant root xylem development is affected by salt stress remains unclear. Using molecular and genetic techniques and detailed phenotypic analyses, we demonstrate that salt causes distinct effects on Arabidopsis seedling root xylem and reveal underlying molecular mechanisms. Salinity causes intermittent inhibition of protoxylem cell differentiation, generating protoxylem gaps, in Arabidopsis and several other eudicot seedlings. The extent of protoxylem gaps in seedlings positively correlates with salt tolerance. Reduced gibberellin signalling is required for protoxylem gap formation. Mutant analyses reveal that the xylem differentiation regulator VASCULAR RELATED NAC DOMAIN 6 (VND6), along with secondary cell wall producing and cell wall modifying enzymes, including EXPANSIN A1 (EXP1), are involved in protoxylem gap formation, in a DELLA‐dependent manner. Salt stress is likely to reduce levels of bioactive gibberellins, stabilising DELLAs, which in turn activates multiple factors modifying protoxylem differentiation. Salt stress impacts seedling survival and formation of protoxylem gaps may be a measure to enhance salt tolerance.